2020
DOI: 10.1080/17461391.2020.1773934
|View full text |Cite
|
Sign up to set email alerts
|

Training intensity distribution analysis by race pace vs. physiological approach in world‐class middle‐ and long‐distance runners

Abstract: This study aimed to analyse the training intensity distribution (TID) of a group of 7 world-class middle-and long-distance runners over 50 weeks using two different approaches to organise TID zones: (1) based on individual specific race pace and;(2) based on physiological parameters. Analysed training data included training volume, intensity and frequency. The average weekly volume for the group was 135.4 ± 29.4 km•week −1 . Training volumes for Z1, Z2 and Z3 were 88.5 ± 1.1%, 7.4 ± 0.8% and 4.1 ± 0.7% respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(113 citation statements)
references
References 26 publications
5
108
0
Order By: Relevance
“…Modern endurance training practice among elite performers in numerous sports [110][111][112][125][126][127][128][129][130][131][132] is dominated by frequent sessions and high total volumes of low intensity training combined with smaller volumes of high intensity training organized as 2-4 "key workouts" in most training weeks. This training organization also holds true for well-trained and worldleading middle-distance runners [10,16,17,133], although 800-m runners apply a greater proportion of training at higher intensities than 1500-m runners (see Sect. 6.3).…”
Section: Variation and Periodizationmentioning
confidence: 90%
See 2 more Smart Citations
“…Modern endurance training practice among elite performers in numerous sports [110][111][112][125][126][127][128][129][130][131][132] is dominated by frequent sessions and high total volumes of low intensity training combined with smaller volumes of high intensity training organized as 2-4 "key workouts" in most training weeks. This training organization also holds true for well-trained and worldleading middle-distance runners [10,16,17,133], although 800-m runners apply a greater proportion of training at higher intensities than 1500-m runners (see Sect. 6.3).…”
Section: Variation and Periodizationmentioning
confidence: 90%
“…Interestingly, the difference in running volume between 800-and 1500-m runners is larger than the difference between 1500and long-distance/marathon runners. World-leading 5-10 km athletes run 120-200 km•week −1 [10,[62][63][64], while topclass marathon runners cover 150-250 km•week −1 [62][63][64]. Based on these running volume distinctions, one could argue that 1500-m runners in general are more long-distance than middle-distance athletes, although high finishing speed is required in slow races [80].…”
Section: Training Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Hommel et al [39] showed that healthy male adults increased the power in MLSS after 1-h LIE at 1.5 to 2.5 mmol•L −1 La − , three days per week for 4 and 6 weeks. To improve endurance performance, the distribution of training intensity in world-class middle-and long-distance runners suggests over 87% of zone 1 (<2 mmol•L −1 ) per week from the general preparation phase [54].…”
Section: Discussionmentioning
confidence: 99%
“…and a pyramidal structured TID (Z1: 79.6% ± 7.2%, Z2: 17.0% ± 6.3%, Z3: 3.4% ± 2.0%; Pol-Index: 1.2 a.u.) when the training zones where quantified on HR [7]. Kenneally et al recently created a novel way to determine endurance intensity zones in middle-and longdistance running based on the relative intensity of the athletes' competition performance (percentage of race pace) [7,8].…”
Section: Introductionmentioning
confidence: 99%